Empowering Rural Communities Through Digital Solutions: A Cultural Immersion Initiative by theEducationalTechnologyStudy Programof UKI Toraja for International Students - Ervianti, Ervianti; Pratama, Muh. Putra; Hasni, Hasni; Pertiwi, Anna; Pairunan, Leadys Ananda Tri (Jurnal Literasiologi, 2024)
This research explores the impact of cultural immersion on the development and implementation of digital solutions in rural Toraja. This study adopts a qualitative research design to explore the impact of digital solutions on empowering rural communities within the context of a cultural immersion initiative. The study employs a case study method, focusing on a specific rural community in Toraja, Indonesia, where international students from the Educational Technology Study Program of UKI Toraja were engaged. The participants in this study included international students enrolled in the Educational Technology Study Program at UKI Toraja, faculty members who facilitated the immersion program, and members of the rural community in Toraja where the immersion took place. The international students were selected based on their participation in the program, while community members were chosen to reflect a diverse range of ages, occupations, and involvement in local cultural practices. In total, 20 international students, 5 faculty members, and 15 community members participated in this study. Data collection was conducted over a three-week period during the cultural immersion program. The primary data collection methods included participant observation and in-depth interviews. The data collected were analyzed using thematic analysis. The study result confirms that the impact of cultural immersion on the development and implementation of digital solutions in rural Toraja are lays on empowerment through digital literacy and cultural sensitivity and adaptation.